Editorial: Shaping Entrepreneurial Attitudes - Wit Pasierbek; Bożena Pera (Jesuit University Ignatianum in Krakow, 2019)
In today's economy, entrepreneurship is considered an important determinant of economic, technological and social development, therefore education in this area, shaping active attitudes and intentions, especially among young people, is an important challenge facing the entire education system, covering all its stages, going beyond its traditional framework and taking into account the assumptions of the lifelong learning concept...